2006
DOI: 10.2298/jsc0612281m
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric analysis of the total lipids extracted from the fatty tissue of fallow deer (Cervus Dama dama L)

Abstract: Thermogravimetry, TG, of lipids is an appropriate analytical method, commonly used to correlate the kinetic parameters of the thermal degradation of lipids and their composition. Thus, samples of total lipids extracted from the raw fatty tissue of fallow deer were subjected to non-oxidative and oxidative TG analysis. The samples were previously stored for nine months at +4 ?C and -18?C. The material stability was investigated in order to establish the most favorable conditions for the production and storage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Other than DSC, TGA has been widely applied in the monitoring of oxidative stability, thermal behavior, kinetic parameters and activation energy in various oil samples [13][14][15][16][17] . It can also be used to determine fraction volatile components by monitoring the weight change as the sample is heated.…”
Section: Introductionmentioning
confidence: 99%
“…Other than DSC, TGA has been widely applied in the monitoring of oxidative stability, thermal behavior, kinetic parameters and activation energy in various oil samples [13][14][15][16][17] . It can also be used to determine fraction volatile components by monitoring the weight change as the sample is heated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Delplancke et al (2018) study referred to by Petrone et al (2020) demonstrates that these metabolites are found at significantly increased concentrations in the hair of pregnant women with gestational diabetes mellitus, rather than as major lipid components. The survival of fatty acids attributed to brain and hair seems inconsistent with temperatures sufficiently high for the vitrification of wood (482-524°C; Petrone et al 2020, Sup Figure S5), at which temperatures not only are these fatty acids volatile, but also unstable (Milovanović et al 2006;Li et al 2018).…”
Section: Lipid Chemistrymentioning
confidence: 99%